To the distribution of the dispersion equation roots for the parametric Cherenkov radiation - Tkachenko, V.I.; Tkachenko, I.V.; Tolstoluzhsky, A.P.; Khizhnyak, S.N. (Вопросы атомной науки и техники, 2020)
Distribution of the roots of dispersion equation of the parametric Cherenkov radiation (PCR) excited by uniformly moving charged particle in an ideally conducting metal waveguide filled with a spatially periodic layered dielectric is studied. The study both in long wavelengths range and in the range of wavelengths comparable and smaller than the period of non-uniformity is presented. It is shown that in the case of long wavelengths the dependence of the frequency of the excited PCR on the particle velocity is monotonic. For the case of wavelengths comparable and shorter than the non-uniformity period the spectrum of PCR is more complicated. Its characteristic features are determined. Досліджується розподіл коренів дисперсійного рівняння параметричного черенковського випромінювання (ПЧВ), збуджуваного зарядженою частинкою, що рівномірно рухається в ідеально провідному металевому хвилеводі, заповненому просторово-періодичним шаруватим діелектриком як в області довгих хвиль, так і в діапазоні довжин хвиль, порівнянних і менших, ніж період неоднорідності. Показано, що у випадку довгих хвиль залежність частоти збуджуваного ПЧВ від швидкості частинки є монотонною. У випадку довжин хвиль, порівнянних і більш коротких, ніж період неоднорідності, спектр ПЧВ більш складний. Визначені його характерні особливості. Исследуется распределение корней дисперсионного уравнения параметрического черенковского излучения (ПЧИ), возбуждаемого равномерно движущейся заряженной частицей в идеально проводящем металлическом волноводе, заполненном пространственно-периодическим слоистым диэлектриком как в области длинных волн, так и в диапазоне длин волн, сопоставимых и меньших, чем период неоднородности. Показано, что в случае длинных волн зависимость частоты возбуждаемого ПЧИ от скорости частицы является монотонной. В случае длин волн, сравнимых и более коротких, чем период неоднородности, спектр ПЧИ более сложный. Определены его характерные особенности.